2016
DOI: 10.2217/bmm-2016-0158
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Risk of Developing Cancer in Subjects Carrying SLC52A3 Rs13042395 Polymorphism: Proof from a Meta-Analysis

Abstract: SLC52A3 rs13042395 C>T polymorphism might be a potential biomarker for cancer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%
“…SLC52A3 was essential for absorption of riboflavin, which was a critical component of the mitochondrial electron transport chain, and loss functional mutation of SLC52A3 may lead to Brown‐Vialetto‐Van Laere syndrome, a rare neurological disorder characterized by bulbar palsies and sensorineural deafness 12 . As for the cancer risk, riboflavin supplement was thought to reduce various types of cancer risks, 13 and several cancer risk research found that SLC52A3 SNPs was associated with oesophageal cancer risk, 14‐16 probably activated by NF‐κB p65/Rel‐B 17 . Previous studies also found that SLC52A3 rs13042395 C > T change could promote glioma cancer cell progression and migration in vivo and in vitro 18 .…”
Section: Discussionmentioning
confidence: 99%
“…We firstly detected protein ( Figure S1B). 12 As for the cancer risk, riboflavin supplement was thought to reduce various types of cancer risks, 13 and several cancer risk research found that SLC52A3 SNPs was associated with oesophageal cancer risk, [14][15][16] probably activated by NF-κB p65/Rel-B. 17 Previous studies also found that SLC52A3 rs13042395 C > T change could promote glioma cancer cell progression and migration in vivo and in vitro.…”
Section: Slc52a3 Regulates Malignant Phenotype Of Gastric Cancer Cementioning
confidence: 99%